Circulating mitochondrial DNA as a biomarker of survival in rheumatoid arthritis-associated interstitial lung disease. Issue 1 (19th January 2023) - Yoon, Hee-Young; Park, Jong Sun; Lee, Sang Eun; Moon, Su-Jin; Song, Jin Woo
Clinically evident interstitial lung disease (ILD) occurs in 10% of patients with rheumatoid arthritis (RA) and is associated with considerable morbidity and mortality [1. RA-associated ILD (RA-ILD) has a poor prognosis with a highly variable and unpredictable clinical course [2]. Although several prognostic factors, including older age, male sex, reduced lung function, and a usual interstitial pneumonia (UIP) pattern or extensive disease on high-resolution computed tomography (HRCT) have been proposed [3], their predictive capacity may be limited by insufficient respiratory effort or interobserver variability. Circulating free mitochondrial DNA (mtDNA) is released from dying cells into the circulatory system in response to injury [4] and is associated with the pathogenesis of various conditions, including ILD [5–8]. Circulating mitochondrial DNA might be a useful prognostic biomarker in patients with rheumatoid arthritis-associated interstitial lung disease https://bit.ly/3HFqhQM